2019
DOI: 10.3390/molecules24193514
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Recovery of Ultralow-Loaded Platinum Anode Electrodes upon Carbon Monoxide and Hydrogen Sulfide Exposure

Abstract: The effects of carbon monoxide (CO) and hydrogen sulfide (H2S) in concentrations close to their respective limits in the Hydrogen Quality Standard ISO 14687-2:2012 on the performance of proton exchange membrane fuel cells (PEMFCs) with ultralow-loaded platinum anode catalyst layers (CLs) were investigated. The anodic loadings were 50, 25, and 15 µg/cm2, which represent the current state-of-the-art, target, and stretch target, respectively, for future automotive PEMFCs. Additionally, the effect of shut-down and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Most studies in literature employ CV scan rates between 1 and 100 mV/s [20,21,26,42,43]. At higher scan rates, current magnitudes arising from electrochemical surface processes generally increase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies in literature employ CV scan rates between 1 and 100 mV/s [20,21,26,42,43]. At higher scan rates, current magnitudes arising from electrochemical surface processes generally increase.…”
Section: Resultsmentioning
confidence: 99%
“…Platinum loadings of 50 μg/cm 2 are already often considered state-of-the-art, with even lower (ultra-low) loadings forecasted for the near future. Although the majority of studies in literature focuses on the cathode electrode including higher catalyst loadings and its decay during accelerated stress tests (ASTs), the anode electrode is of interest especially when investigating the effect of startup/shutdown cycles [24] or impurities [25,26] on the anode compartment, or the cell reversal tolerance upon freeze start-ups and successional reversal effects [27,28]. Therefore, thorough understanding of CVs of low-and ultra-low-loaded electrodes is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…All of these species are included in the hydrogen fuel standard [5]. For CO and H 2 S, a lower Pt or PtRu catalyst loading generally leads to an increase in the anode overpotential [6][7][8][9][10]. However, it was reported that for H 2 S, the catalyst loading effect disappears for values equal to or below 25 µg cm −2 [10].…”
Section: Introductionmentioning
confidence: 99%
“…For CO and H 2 S, a lower Pt or PtRu catalyst loading generally leads to an increase in the anode overpotential [6][7][8][9][10]. However, it was reported that for H 2 S, the catalyst loading effect disappears for values equal to or below 25 µg cm −2 [10]. An effect was not observed with the weak contaminant CO 2 , which is attributed to a concentration that was substantially lower (1%) [7] than in a typical reformate (10-20%) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we note that alternative strategies, such as hydrogen purification, can contribute to the restriction of CO poisoning in H 2 -PEMFCs. Prass et al [163] investigated platinum catalyst layers with ultralow metal loadings (50, 25, and 15 µg cm −2 ) in order to mitigate CO contamination according to the Hydrogen Quality Standard ISO 14687-2:2012 limits for PEMFCs. The authors, based on the relatively high overpotentials that occurred due to CO poisoning and their assumption that the use of slightly anodic loadings is inevitable for PEMFC commercialization, suggested that the research community should consider focusing on reducing the CO concentration limits of the Hydrogen Quality Standard.…”
mentioning
confidence: 99%